SCALE UP UMKM THROUGH DIGITALIZATION, FINANCIAL LITERACY AND BUILDING AN INTERNAL CONTROL SYSTEM AT SORCHA LAUNDRY - Ramdani, Dani; Maghriby, Bimbim; Nirwan, Nirwan (LPPM Univ. Ibn Khaldun Bogor, 2023)
Sorcha laundry is an MSME in Bandung City that was established in 2021. Sorcha laundry is determined to become a laundry retail that serves all types of customer laundry, ranging from kilo items, premium units, bed covers, linens, baby strollers, shoes, bags, to carpet washing services. The problem faced by Sorcha laundry is that it wants to develop its business by opening many branches in Indonesia, does not understand the importance of branding, does not have good financial literacy, is less adaptive to digitalization, bookkeeping is still manual, does not have a standard system so it is difficult to develop its business. Then the solution to solve the problem is: 1). Build branding with a good build design outlet, Co Branding with Key Opinion Leader/ influencer. 2). Financial literacy training and applying cashless payment / Quick Response Code Indonesian Standard (QRIS). 3). Training on digitizing and applying online orders through ads on Instagram and Google ads. 4). Accounting training and using Point Of Sales (POS) System. 5). Create Standard Operational Procedure (SOP) & create Command Center to monitor stores remotely using CCTV IP Address technology that can be monitored realtime.